Deconstruction of cellulosic fibers to fibrils based on enzymatic pretreatment. (November 2018) - Wang, Shengdan; Gao, Wenhua; Chen, Kefu; Xiang, Zhouyang; Zeng, Jinsong; Wang, Bin; Xu, Jun
Graphical abstract: Highlights: An efficient and economical enzymatic pretreatment technology was developed. The obvious fibrillation of fiber was obtained by commercial endoglucanase pretreatment. Marked disintegration of fibers was occurred at high fiber recovery of 100%. The effects of pretreatment time on microstructure features have been determined. Abstract: Enzymatic pretreatment has shown great potential in making the disintegration of cellulosic fibers to fibrils cost-effectively and environmental-friendly. In this study, an extensive commercial endoglucanase was used to pretreat cellulosic fibers for fibrillation. The pretreatment time and the enzyme dosage were optimized using response surface methodology. A 100% fiber recovery was obtained at endoglucanase usage of 9.0 mg/g (substrate) and pretreatment time of less than 3.0 h. A highly fibrillated and fractured surface of pretreated fibers was observed after 0.5 h of pretreatment compared to native fibers. Meanwhile, the progressive deconstruction of cellulosic fibers was occurred with the enzymatic pretreatment time increasing. The degree of deconstruction of fibers was evidenced by changes of the fiber microstructure, such as the inter-/intra-molecular H-bonds, the β-1, 4-glucosidic linkages, crystallinity and crystallite size. These discoveries provide new insights into a more efficient and economic pretreatment methods for the disintegration of fibrils from cellulosic fibers.